AN ANALYSIS THE USE OF KAHOOT MEDIA IN THE COOPERATIVE GRAMMAR LEARNING PROCESS AT SCHOOL - Idris P, Muh.; Rampeng, Rampeng (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This study aimed to analyze the use of Kahoot media in cooperative grammar learning through the students' learning process at school. Data collection techniques used literature study. Researchers took seven articles and then analyzed them qualitatively. The results showed that the use of Kahoot media in the cooperative grammar learning process has a positive impact on students. Students continued to be ambitious in learning even before learning began. Students' grades were better at capability. They performed fewer mistakes and were more enthusiastic. The learning condition was fun and effective in motivating students in learning, especially learning foreign languages. Therefore, it is suggested to use Kahoot as a medium of the teaching-learning process.